Continuous monitoring of summer surface water vapor isotopic composition above the Greenland Ice Sheet - H. C. Steen Larsen; S. J. Johnsen; V. Masson Delmotte; C. Risi; H. Sodemann; D. Balslev Clausen; T. Blunier; D. Dahl Jensen; M. D. Ellehøj; S. Falourd; A. Grindsted; V. Gkinis; et al. (Atmospheric Chemistry and Physics, 2013)
We present here surface water vapor isotopic measurements conducted from June to August 2010 at the NEEM (North Greenland Eemian Drilling Project) camp, NW Greenland (77.45 degrees N, 51.05 degrees W, 2484 m a.s.l.). Measurements were conducted at 9 different heights from 0.1m to 13.5m above the snow surface using two different types of cavity-enhanced near-infrared absorption spectroscopy analyzers. For each instrument specific protocols were developed for calibration and drift corrections. The inter-comparison of corrected results from different instruments reveals excellent reproducibility, stability, and precision with a standard deviations of similar to 0.23 parts per thousand for delta O-18 and similar to 1.4 parts per thousand for delta D. Diurnal and intraseasonal variations show strong relationships between changes in local surface humidity and water vapor isotopic composition, and with local and synoptic weather conditions. This variability probably results from the interplay between local moisture fluxes, linked with firn-air exchanges, boundary layer dynamics, and large-scale moisture advection. Particularly remarkable are several episodes characterized by high (> 40 parts per thousand) surface water vapor deuterium excess. Air mass back-trajectory calculations from atmospheric analyses and water tagging in the LMDZiso (Laboratory of Meteorology Dynamics Zoom-isotopic) atmospheric model reveal that these events are associated with predominant Arctic air mass origin. The analysis suggests that high deuterium excess levels are a result of strong kinetic fractionation during evaporation at the sea-ice margin.